2005
DOI: 10.1080/07357900500202820
|View full text |Cite
|
Sign up to set email alerts
|

Does Simian Virus 40 Cause Non-Hodgkin Lymphoma? A Review of the Laboratory and Epidemiological Evidence

Abstract: Recently, several studies have reported the detection of DNA from simian virus 40 (SV40), a macaque polyomavirus, in tumor tissues obtained from non-Hodgkin lymphoma (NHL) patients. SV40 accidentally contaminated poliovirus vaccines administered to millions of individuals in 1955-1962. A link between SV40 and NHL is biologically plausible because SV40 causes hematological malignancies in laboratory rodents. However, detection of SV40 DNA in human NHL tumors has not been confirmed by other laboratories. Casting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The debate on the possible adverse effects of SV40 for humans has been contentious 9, 10, 11, 12, 13, 14, 15, 16, 17, 18. High rates of recovery of SV40 DNA sequences from cancer tissues have led some investigators to propose that SV40 infection may have a role in the development of mesothelioma, brain tumors, osteosarcoma and NHL.…”
Section: Introductionmentioning
confidence: 99%
“…The debate on the possible adverse effects of SV40 for humans has been contentious 9, 10, 11, 12, 13, 14, 15, 16, 17, 18. High rates of recovery of SV40 DNA sequences from cancer tissues have led some investigators to propose that SV40 infection may have a role in the development of mesothelioma, brain tumors, osteosarcoma and NHL.…”
Section: Introductionmentioning
confidence: 99%
“…28 In vitro experiments have shown that SV40 large T antigens promote transformation by binding and inactivating the products of several tumor suppressor genes, particularly P53. 28,29 Despite these suggestions of a possible link between SV40 and P53 accumulation, no previous studies have investigated the potential implication of the SV40 in such accumulation of P53 protein in diffuse large B-cell lymphomas.…”
mentioning
confidence: 99%
“…Some groups indicated an association between NHL and SV40 by reporting a high prevalence of SV40 Tag coding sequences at up to 43% [1][2][3]. Other investigators have not confirmed the association [6]. Differing prevalence levels of SV40 infection, detected in human populations of distinct origin, could be due to living parameters and hygiene conditions [7].…”
Section: Introductionmentioning
confidence: 99%